(untitled) (Medical Forum Monthly, 2026)
Objective: To compare the length of hospital, stay in patients undergoing cemented total hip arthroplasty who were mobilized on the day of surgery versus those mobilized on the first postoperative day. Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the Department of Orthopedic Surgery, Unit I, King Edward Medical University/Mayo Hospital, Lahore, Pakistan, from January 2025 to June 2025. Methods: A total of 180 patients aged 40–70 years undergoing cemented total hip arthroplasty were randomly allocated into two groups (n=90 each). Group A patients were mobilized on the day of surgery, while Group B patients were mobilized on the first postoperative day. Hospital stay was recorded in hours from surgery to discharge. Data were analyzed using SPSS version 21, and an independent sample t-test was applied. Results: The mean age was 56.36±8.27 years in the early mobilization group and 55.49±9.17 years in the control group, with females constituting 63.9% of participants. The overall mean hospital stay was 64.52 ± 9.43 hours. Patients mobilized on the day of surgery had a significantly shorter hospital stay (60.82±7.61 hours) compared with the control group (68.21±9.65 hours) (p=0.001). Conclusion: Day-of-surgery mobilization after cemented total hip arthroplasty significantly reduces hospital length of stay compared with conventional postoperative mobilization.